Comparative Insights into Smallholder Agriculture in Uttar Pradesh and Rajasthan: A Field Study - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2020)
Field visits were undertaken to speak to farmers in some districts in Uttar Pradesh and Rajasthan to gain some qualitative insights about their current experiences with agriculture. The conversations were around production costs, prices of produce, economic viability of smallholder agriculture and agriculture extension services. Other issues connected to agriculture like landholding sizes, leasing of agricultural land, government policies and schemes for agriculture like minimum support prices (MSP), agriculture credit/Kisan Credit Cards(KCC), Soil health Cards (SHC), input subsidies etc., were also discussed. This paper summarises these free flowing discussions. Criticality of irrigation, comparisons between small and marginal farmers as compared to the slightly more landed farmers, agriculture being no longer remunerative enough and consequent disillusionment of farmers and youth with agriculture as a sole means of livelihood are general themes that emerge from these conversations. Paper concludes by elaborating these themes and observing that in spite of inadequate economic returns, smallholder agriculture in India remains significant for food security and livelihoods of our farmers in the absence of alternate and better remunerating economic opportunities.
Keywords: 330